Analisis Daya Saing Ekspor Indonesia Produk Kopi panggang ke Kawasan ASEAN Berdasarkan Metode Revealed Comparative Advantage - Favian Jihan Prastian; Farida Pulansari (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Export means transporting or bringing goods and services from one country to another coun-try. In order to evaluate how strong export competitiveness is and identify market opportunities, specific calculation methods and approaches regarding comparative advantage are needed. One of them is using the "revealed comparative advanced" (RCA) method, which provides an accu-rate picture of how competitive a product is in the international market. One measuring tool is the Balassa index, where a value of more than one (>1) indicates a strong level of competitive-ness for export products to the destination country. Conversely, a value less than one (<1) indi-cates low competitiveness and sales difficulties in that market. The calculation results show that Timor Leste has an average Balassa index of 60.685, followed by Brunei Darussalam with a Balassa index value of 12.526 and Malaysia of 4.987 and with a stable value, thus indicating good potential for exporters who want to market coffee products. roast them to the country. However, Thailand has little potential with a Balassa index of 1.944. In contrast, Singapore and the Philippines have an average Balassa index below 1, indicating there is no great potential as a profitable export market.